IMPLEMENTASI PROGRAM CSR BIDANG PENDIDIKAN PT ANTAM DI KECAMATAN TAYAN HILIR KABUPATEN SANGGAU - Asvia, Mustaan Hamid; Mashudi, Mashudi; Maria, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was conducted in Tayan Hilir District, Sanggau Regency. The purpose of this study is to find out how far the implementation of the CSR (Corporate Social Responsibility) program that has been carried out by PT Antam in the field of education has been. The research approach used is in the form of qualitative research in the form of interactive inquiry. The results of interviews and observations with 6 informants consisting of 1 person as Secretary of Inland Village, 1 person as ER and CSR Department Head, 1 person as representative of student beneficiaries, and 3 people as beneficiaries of school representatives. Data were collected using closed interview and observation methods as well as several documents relevant to the research. The results of the study found that the implementation of PT Antam's CSR program in the field of education in Tayan Hilir District, Sanggau Regency had been going well and according to a predetermined plan, but the implementation of the program was still unable to accommodate all the needs and problems in the education sector in the area where they carried out their business activities.